Increased Insulin Concentrations During Growth Hormone Treatment in Girls With Turner Syndrome Are Ameliorated by Hormone Replacement Therapy - Segerer, Sabine Elisabeth; Segerer, Stephan Georg; Partsch, Carl-Joachim; Becker, Wolfgang; Nawroth, Frank (Frontiers in Endocrinology, 2020)
Objective: Turner syndrome (TS) is characterized by complete or partial loss of one sex chromosome and is commonly associated with short stature, metabolic changes (such as central obesity, abnormal glucose tolerance and high triglycerides) and premature ovarian insufficiency (POI). Primary management of TS during childhood and adolescence comprises treatment with human growth hormone (hGH) and, in cases with early loss of ovarian function, hormone replacement therapy (HRT). Given that metabolic parameters are altered when HRT is applied during menopause, we analyzed whether metabolic changes might be positively or negatively affected within 10 years after HRT and/or hGH in girls with TS. Design: Observational study. Methods: Data were collected from the medical records of 31 girls with TS attending two endocrinologic centers in Germany between 2000 and 2020. Descriptive statistics are reported as the mean ± SEM or percentages. Results: The mean age at first presentation was 99.06 ± 8.07 months, the mean height was 115.8 ± 3.94 cm, and the mean BMI 19.0 ± 0.99 was kg/m2. Treatment with hGH was given to 96.8% of the girls, starting at an average age of 99.06 ± 8.70 months, and was continued for 67.53 ± 6.28 months. HRT was administered to 80.6% of all patients and was started at a mean age of 164.4 ± 4.54 months. During the follow-up, we did not observe any significant absolute changes in lipid parameters, but we detected beneficial effects of childhood hGH: significantly lower cholesterol (-0.206/month; p=0.006), lower low density lipoprotein cholesterol (-0.216/month; p=0.004) and higher high density lipoprotein cholesterol (+0.095/month; p=0.048). Insulin concentrations, showed a significant increase attributable to hGH treatment (+0.206/month; p=0.003), which was ameliorated by concomitant or subsequent HRT (-0.143/month; p=0.039). Conclusion: Treatment with hGH as well as HRT is provided to most girls with TS. Metabolic effects are associated with both modalities. Monitoring of metabolic changes appears to be important to detect unfavorable effects, and could guide treatment adjustment and duration.